Rafael Lucas Rodríguez Caballero: humanist, botanist and conservacionist - Rodríguez Sevilla, Rafael Lucas (2022)
Rafael Lucas Rodríguez Caballero was a humanist, botanist, and conservationist. He graduated simultaneously with a Bachelor of Science, from the University of Costa Rica (UCR) and with a Master of Arts from the University of California, Berkeley, in 1948. And he graduated with a Ph. D. in Botany, also from the University of California, Berkeley, in 1953. He founded the School of Biology of the University of Costa Rica. There he carried out a monumental work: with a great genius for teaching science, he trained several generations of top-level biologists; he trained and recruited world-class teachers to increase the quality of the School; and he conducted research that draws attention to the present, both for its scope, and for the quality of his illustrations. He was the founder or co-founder of the UCR University Choir, the College of Biologists, and the Organization for Tropical Studies (OET). He supported the Revista de Biología Tropical for decades, and enthusiastically supported the Central American Institute for Cultural Extension (ICECU) and the Costa Rican Institute for Radio Education (ICER), as well, for decades. In addition, he orchestrated the creation of the Lankester Garden, which initially rescued Charles Lankester's magnificent living collection of orchids, and is now a center of international caliber for orchidology. He won numerous and diverse national and international distinctions, some of them even after his death in 1981.